Organizing the Unemployed: Community and Union Activists in the Industrial Heartland - Rachleff, Peter (Labour / Le Travail, 1998)
The article reviews the book, "Organizing the Unemployed: Community and Union Activists in the Industrial Heartland," by James J. Lorence.